Relationship Between Mother's Parity and Knowledge of Care ror Newborn Baby of Primitary Mothers at Tumpunglaung Public Health Center - Nunik Suhartyny; Sulistiyah Sulistiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Maternal knowledge of newborn care plays an important role in maintaining neonatal health and preventing early complications. Parity is considered one of the factors that affect the mother's level of knowledge, as previous childbirth experiences can improve the understanding and skills of caring for the baby. However, primipara mothers often face challenges due to limited experience. This study aims to analyze the relationship between parity and newborn care knowledge in primipara mothers at the Tumpunglaung Health Center. The research method uses an analytical quantitative design with a cross-cutting approach. The study population was mothers who had just given birth at the Tumpunglaung Health Center, with a sample of 30 primipara mothers selected through purposive sampling. Data were collected using a structured questionnaire that included maternal characteristics and newborn care knowledge, including breastfeeding, hygiene, thermoregulation, and red flags. Data analysis was carried out by Chi-square test using SPSS at a significance level of p < 0.05. The results showed that most primitive mothers had moderate to low levels of knowledge, with a significant relationship between parity and newborn care knowledge. The conclusion of the study confirms the importance of strengthening education and counseling for primitive mothers to improve infant care practices and support neonatal health.